The Relationship Between Spiritual Wellbeing With Medication Adherence in Hypertensive Patients Referred to Selected Heart Clinics of Iran University of Medical Sciences, Iran, 2020 - Reza Amiri; Marjan Mardani-Hamooleh; Mansoureh Ashghali Farahani; Mahnaz Ghaljeh; Shima Haghani (Iran University of Medical Sciences, 2021)
Background & Aims: Epidemiological changes have made chronic diseases increasingly important. Hypertension is also known as a chronic disease. The high prevalence of hypertension has made the disease a significant health problem in communities. Spiritual health has been proposed as one of the health indicators and predictors of self-care in chronic diseases. This study aimed to determine the relationship between spiritual health and adherence to the treatment regimen in patients with hypertension. Materials & Methods: In this descriptive correlational study, 121 patients with hypertension were selected by continuous sampling method from cardiac clinics affiliated with Iran University of Medical Sciences, Iran, in 2020. The study data were collected through demographic information form and validated Ellison and Paloutzian spiritual health and Hil-Bone diet adherence questionnaires. For data analysis, we performed the statistical tests of the Spearman, independent t test, Chi-square, and analysis of variance in SPSS version 16. Results: This study shows a significant and negative relationship between spiritual health and adherence to the treatment regimen in patients with hypertension (P=0.001, r=-0.05). Conclusion: As spiritual health increases, adherence to the treatment regimen in patients with hypertension decreases. Spiritual health in this group of patients leads to less adherence to the treatment regimen.